Respuesta :
Answer:
y = x + 1
Step-by-step explanation:
We can use the point-slope formula to write an equation for this problem. The point-slope formula states: (y - y1) = m (x - x1)
Where m is the slope and (x1 y1) is a point the line passes through.
Substituting the slope and the values from the point in the problem gives:
( y - 2 ) = 1 ( x - 1 )
We can also solve for y to put the equation in slope-intercept form. The slope-intercept form of a linear equation is: y = mx + b
y - 2 = 1x - 1
y = 1x - 1 + 2
y = 1x + 1 or y = x + 1 * are just the same.
Answer:
y=-x+3
Step-by-step explanation:
Since we are given the slope m = −1 of the line and the point (x1,y1)=(1,2) on the line, we can substitute these values into the point-slope form of a line, y − y1= m(x − x1). The slope is:
Slope: m= −1
The point given is:
Point:( 1, 2)
Substituting these values into y−y1=m(x−x1) and rewriting the resulting equation in point-slope form gives:
y-(2)=-1(x-(1))
y-2=-x+1
y=-x+3